1993
DOI: 10.1002/hup.470080609
|View full text |Cite
|
Sign up to set email alerts
|

Use and awareness of effects of anabolic steroids and psychoactive substances among a cohort of nigerian professional sports men and women

Abstract: In 1992, 250 professional sports people (72 per cent males, mean age 25 years), mostly among those invited for screening for the Olympics, completed a questionnaire, aimed at highlighting the prevalence of use of anabolic steroids and other psychoactive substances, and the factors associated with the use of drugs.The prevalence of life-time use of drugs was as follows: 1.2 per cent for anabolic steroids, 0.8 per cent for amphetamines, 0.4 per cent for cocaine, 0.8 per cent for cannabis and 5.6 per cent for cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…According to a study on the high- level endurance walkers, they could mention just an average of 1.5 drugs of the list of prohibited doping drugs ( 6 ). Another research regarding health consequences of doping drugs demonstrated that only 20% of the Nigerian athletes were familiar to the side effects of anabolic steroids such as tendon injuries, acne or gynecomastia ( 7 ). In another study on French high school athletes, participants mentioned peers or health professionals as the main source of drug supply.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study on the high- level endurance walkers, they could mention just an average of 1.5 drugs of the list of prohibited doping drugs ( 6 ). Another research regarding health consequences of doping drugs demonstrated that only 20% of the Nigerian athletes were familiar to the side effects of anabolic steroids such as tendon injuries, acne or gynecomastia ( 7 ). In another study on French high school athletes, participants mentioned peers or health professionals as the main source of drug supply.…”
Section: Introductionmentioning
confidence: 99%
“…Seven percent of them did not believe that doping is always a dangerous behavior ( 8 ). A study on 80 weight-lifters showed that the anabolic steroid users found physicians as no more reliable than their friends, internet sites, or the persons who sold them the steroids ( 7 ). In another project, 155 American athletes participating in winter games (1992) were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…45 Also, 5.6% of Nigerian professional athletes reported using codeine at some point in the past. 52 Other medications used for pain Reported rates of non-NSAID oral analgesic medications ranged from 0.4% of players at the 2007 under-20's World Cup 11 to 20% among elite Italian cyclists in the previous three months. 45 Often, such medication use was reported simply as "analgesic" rather than specifying what types of non-NSAID medications, such as paracetamol.…”
mentioning
confidence: 99%
“…2% of elite athletes use PEDs and this figure has been fairly stable over the past 5 years (WADA, 2007). Prevalence rates derived from self-report typically range between 1.2% and 26% (Ohaeri et al, 1993;Ama et al, 2003;Ö zdemir et al, 2005;Papadopoulos et al, 2006;Backhouse et al, 2007;Petroczi, 2007;Tahtamouni et al, 2008), with the high end being associated with a specific population such as bodybuilders. Morgan (2006) underscores the unreliability of prevalence estimates by stating that ''anecdotal evidence'' for doping prevalence could be as low as 5% and as high as 95%.…”
mentioning
confidence: 99%